2018
DOI: 10.1097/qai.0000000000001762
|View full text |Cite
|
Sign up to set email alerts
|

HIV Pre-Exposure Prophylaxis Stigma as a Multidimensional Barrier to Uptake Among Women Who Attend Planned Parenthood

Abstract: Findings highlight the need for positive messaging targeting potential PrEP users and their social networks to increase PrEP acceptance and uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 26 publications
4
79
0
Order By: Relevance
“…To develop the HPSS, we reviewed literature regarding PrEP stigma and identified key sources for items: a study of stigma as a multidimensional barrier, [34] studies of barriers and facilitators to PrEP acceptability, [35,36] measures from the Adolescent Medicine HIV Trials Network for HIV/AIDS Interventions (ATN) U19 Scale It Up, [37,38] and measures from an HIV Prevention Trials Network Study, HPTN082 [39,40]. We sought to include studies representing a broad range of characteristics; in total, there were 1586 participants in these studies, including 402 men, 1171 women, and 7 transgender men; 824 heterosexual, 140 bisexual, and 154 gay/homosexual persons; 666 Black, 250 White, 184 Latino, and 13 Asian; and 400 participants from international settings.…”
Section: Scale Developmentmentioning
confidence: 99%
“…To develop the HPSS, we reviewed literature regarding PrEP stigma and identified key sources for items: a study of stigma as a multidimensional barrier, [34] studies of barriers and facilitators to PrEP acceptability, [35,36] measures from the Adolescent Medicine HIV Trials Network for HIV/AIDS Interventions (ATN) U19 Scale It Up, [37,38] and measures from an HIV Prevention Trials Network Study, HPTN082 [39,40]. We sought to include studies representing a broad range of characteristics; in total, there were 1586 participants in these studies, including 402 men, 1171 women, and 7 transgender men; 824 heterosexual, 140 bisexual, and 154 gay/homosexual persons; 666 Black, 250 White, 184 Latino, and 13 Asian; and 400 participants from international settings.…”
Section: Scale Developmentmentioning
confidence: 99%
“…Stigma can be particularly high in contexts where community awareness about PrEP is low, cultural norms dictate that unmarried women should not be sexually active or should practice monogamy, and PrEP was initially prioritized for "high-risk" key populations, including female sex workers (FSWs) [14,[19][20][21]. Quantitative analyses among men who have sex with men (MSM) in the United States and Africa and heterosexual women in the United States have found that stigma significantly reduces PrEP interest, uptake and adherence [14,[22][23][24][25][26][27][28]. Stigma may also influence African women's PrEP adherence as shown by qualitative work conducted among AGYW and FSWs that describes women's need to discreetly use HIV prevention products and miss doses because of concerns around stigma [18,19,[27][28][29][30].…”
mentioning
confidence: 99%
“…Our results show that prior to the training, participants had a high awareness of PrEP, high perceived knowledge, but low actual knowledge of PrEP. We observed a statistically significant increase in PrEP stigma has been identified as a major barrier to PrEP uptake and adherence globally [39,52,53].…”
Section: Discussionmentioning
confidence: 74%